Usulan Model Pengembangan Pariwisata Pantai di Kaki Jembatan Suramadu - Utami, Issa Dyah (Rekayasa, 2009)
Suramadu  bridge that  connect between Java Island  with Madura Island  will open opportunity for  Regency  ofBangkalan becomes industrial location of region tourism at East Java: Rongkang beach was one of tourism region at Bangkalan that its positzon  close to Suramadu Bridge. At thzs time tourism area at Rongktlng Beach stills wasn't maximal. To it in observational it was made by model optimal  utmost of  many_ industrial park  management alternatives Rongkang's  Beaches with dynamic system  approaching.  This research proposes  two area  developmental  scenarios Rongkang's  Beach tourzsm. Devefopmental   scenario I of the Beach tourism area Rongkang by nature bY utilizes and pet  beach region authenticity and its vicinity. Scenario II. tourism area Development Rongkang' s Beach by undertaking deve1opment in many region, which is by building umpteen interesting modefor tourism.The result of thzs research was pomt out that scenario II are the best. areas developmental modelling ofRongkang's Beach tourism more reasonable and more advantaKes to be compared with Its I. Scenario I inaicate that the cashflow is Rp. 28. 397. 088. 000,- wzth payback  period    0,352149  years.  Meanwhile  cashflow   of scenario  zs Rp.  667.  942.1.000,- with payoack period  0,149713 years.Key word: Tourism, dynamic system, investment